Documentary sources for the study of the 19th century Brazilian house - Aragão, Solange de (Risco - Journal of Architecture and Urbanism, 2010)
This paper aims to present and discuss four documentary sources for the study of the 19th century Brazilian house: traveler's writings, newspaper advertisements, paintings and landscape photographs; documents in which the Brazilian architecture, specially the house, is described or presented in its external or internal aspects, and sometimes appears as part of Brazilian landscapes.